(untitled) (Research, Society and Development, 2022)
Objective: Discuss the impact of the consumption of ultra-processed foods on children’s health in times of the COVID-19 pandemic. Methodology: Review of narrative literature carried out through a bibliographic search of articles in English and Portuguese, available in the following databases: Scielo, Virtual Health Library (BVS), Google academic and PubMed. Articles with publication dates of the last five years were included. The descriptors used were: “COVID-19”, “Child nutrition”, “Eating habits”. Results: The strategies used to limit the spread of COVID-19, such as social distancing and suspension of classes, have a direct impact on food, with this, there is a greater consumption of ultra-processed and canned foods, as they are easier to acquire, store and store. and have a longer shelf life. This type of food has low nutritional value and high caloric value, is rich in saturated and trans fats, refined carbohydrates and low levels of fiber, unsaturated fat, micronutrients and antioxidants. They act negatively on immunity, causing chronic inflammation, manifestation or worsening of overweight and obesity, impairing the body’s defense against viral pathogens, representing a high risk for the serious pathology of COVID-19. Final considerations: The changes related to the restrictions caused by the pandemic reflected in poor eating habits and, consequently, the worsening of chronic non-communicable diseases. Maintaining a healthy and balanced diet is essential, as it reduces the negative impacts promoted by SARS-Cov2, since fresh foods directly and positively influence the immune system.